2021
DOI: 10.1177/0739986321995910
|View full text |Cite
|
Sign up to set email alerts
|

Skin Color Matters in the Latinx Community: A Call for Action in Research, Training, and Practice

Abstract: While skin color is relevant and important in the Latinx community, as it is associated with colorism, little is known about how often it is measured or the best way to measure it. This article presents results from two studies examining these key concerns in three prominent journals, where Latinx research is typically published (i.e., the Hispanic Journal of Behavioral Sciences, the Journal of Latinx Psychology, and Cultural Diversity and Ethnic Minority Psychology). Study one examined whether skin color was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…These efforts are critical as a disproportionate number of journal editors and authors are White, numerous publications do not underscore the importance of race, and many studies do not include participants of color (Roberts et al, 2020). Moreover, Fuentes et al (2021) found that colorism, which affects many BIPOC individuals, was infrequently and inconsistently measured in Latinx research. Finally, French et al (2020), who provide helpful directions for conducting research on and for BIPOC communities, advocate for more complex research designs that utilize mixed method approaches for examining structural variables.…”
Section: Examining Value Systems In Open Sciencementioning
confidence: 99%
“…These efforts are critical as a disproportionate number of journal editors and authors are White, numerous publications do not underscore the importance of race, and many studies do not include participants of color (Roberts et al, 2020). Moreover, Fuentes et al (2021) found that colorism, which affects many BIPOC individuals, was infrequently and inconsistently measured in Latinx research. Finally, French et al (2020), who provide helpful directions for conducting research on and for BIPOC communities, advocate for more complex research designs that utilize mixed method approaches for examining structural variables.…”
Section: Examining Value Systems In Open Sciencementioning
confidence: 99%
“…Furthermore, as noted above, RES conversations in Asian American and Latinx immigrant families are influenced by the racialized context of their home countries and broader global views regarding colorism and anti-Blackness. For example, darker skinned Latinx adolescents might receive more RES messages from their parents compared to their lighter skinned counterparts, as these parents may themselves have been racialized (Fuentes et al, 2021). These differential messages likely also stem from families navigating complex racial hierarchies in their own home countries, and unfortunately, due to the pervasiveness of anti-Blackness worldwide, these messages may coincide with U.S. racial hierarchies as well (Adames et al, 2016; Chavez-Dueñas et al, 2014; Fuentes et al, 2021).…”
Section: Integrated Model Of Adolescent-directed Res (Adres)mentioning
confidence: 99%
“…For example, darker skinned Latinx adolescents might receive more RES messages from their parents compared to their lighter skinned counterparts, as these parents may themselves have been racialized (Fuentes et al, 2021). These differential messages likely also stem from families navigating complex racial hierarchies in their own home countries, and unfortunately, due to the pervasiveness of anti-Blackness worldwide, these messages may coincide with U.S. racial hierarchies as well (Adames et al, 2016; Chavez-Dueñas et al, 2014; Fuentes et al, 2021). Asian American and Latinx immigrant families may unfortunately espouse anti-Black (or anti-other group) sentiments that they communicate to their adolescents.…”
Section: Integrated Model Of Adolescent-directed Res (Adres)mentioning
confidence: 99%
“…People of Latin American and Caribbean ancestry living in the U.S. make over 18% of the population and employ different terms to identify themselves, including panethnic labels such as Hispanic, Latino/a, Latine, and Latinoamerino, and/or specific labels related to their countries of origin, such as Mexican American, Puerto Rican, and/or Cuban American (Noe-Bustamante et al, 2020). Although they are often considered a monolithic ethnic group, there is considerable variation within Latinx people in terms of skin color, ethnic-racial identity, acculturation, legal status, and migration experience (Cahill et al, 2021;Fuentes et al, 2021).…”
Section: Latinx Youth In the Us Participating In Funerals: "Un Entier...mentioning
confidence: 99%